TIGIT Signaling Pathway Regulates Natural Killer Cell Function in Chronic Hepatitis B Virus Infection - Wang, Juan; Hou, Hongyan; Mao, Lie; Wang, Feng; Yu, Jing; Luo, Ying; Lin, Qun; Sun, Ziyong (Frontiers in Medicine, 2022)
Background and objective: The persistent infection of hepatitis B virus (HBV) and liver damage in immune active chronic hepatitis B (CHB) could be partly due to the over-reaction of NK cells, including pro-inflammatory cytokine secretion and cytotoxicity. An immunosuppressive receptor, T-cell immunoglobulin and immunoreceptor tyrosine–based inhibitory motif (ITIM) domain (TIGIT) is specifically expressed on the NK cells. This study aims to investigate the role of TIGIT signaling pathways in regulating NK cell functions in CHB patients. Method: We comparatively assessed the expression of TIGIT on NK cells of immune active CHB (CHB-IA) patients, immune control chronic HBV carriers (CHB-IC) and healthy controls (HCs) and then explored the mechanisms of TIGIT signaling pathway in regulating NK cell-mediated liver injury using different molecular assessments. Results: TIGIT expression on the NK cells enhanced in the CHB-IC, but reduced in the CHB-IA, compared with that HC group. In the CHB-IA patients, the expression of TIGIT was inversely correlated with intensity of the liver damage. Moreover, TIGIT-NK cells show higher IFN-γ secretion capability, degranulation activity and cytotoxicity, but lower apoptosis than TIGIT+ NK cells. Blockade of TIGIT pathway with anti-TIGIT antibody increased NK cell function, while activation of the TIGIT pathway with TIGIT Fc and CD155 Fc chimera protein down-regulated NK cell functions. Conclusion: Our data showed TIGIT signaling pathway participates in NK cell impairment, which could be used as a new therapeutic target to protect the patients with chronic HBV infection patients from severe liver injury.